2022
DOI: 10.1039/d1na00676b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SERS-active core–satellite nanoparticles using heterobifunctional PEG linkers

Abstract: Here we report the synthesis of core–satellite nanoparticles to explore tunable SERS hot-spot generation, signal reproducibility and long-term activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Therefore, materials that have affinities with metal nanoparticles have been the main targets of detection in related research. [26][27][28] However, most neurotransmitters, including the aforementioned neurotransmitters, have less affinities with metal nanoparticles. 29,30 So, to detect neurotransmitters using SERS, it is necessary to design a method that can attract them close to the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, materials that have affinities with metal nanoparticles have been the main targets of detection in related research. [26][27][28] However, most neurotransmitters, including the aforementioned neurotransmitters, have less affinities with metal nanoparticles. 29,30 So, to detect neurotransmitters using SERS, it is necessary to design a method that can attract them close to the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…2,19 SERS methods utilize the significant Raman scattering amplification afforded by the close association of Raman-active dyes or biomarkers with plasmonic metal nanostructures to detect targets of interest sensitively and specifically. [20][21][22][23][24] SERS-active substrates have been developed for inclusion in diagnostic platforms that may be suitable for POC applications, including paper and microfluidic cartridges. 20 Furthermore, the narrow bandwidths of Raman peaks make the technique an ideal candidate for multiplexed detection due to the ability to resolve multiple peaks of interest within a complex matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (Au-NPs) are employed as enhancers in SERS due to the surface plasmon resonance, which involves collective oscillations of surface electrons of NPs. During the optimization of the performance of NP-based Raman enhancers, reports have shown that the size, shape, and interparticle distance , play a crucial role. However, a detailed correlation between the structure of Au-NP monolayers and their performance as SERS substrates is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%